The Effect of Pregnancy Exercises on the Quality of Sleep of Third Trimester Pregnant Women in Sindangrasa Village Ciamis District - Nurherliyany, Metty; Novianti, Annisa Rizqy; Srinayanti, Yanti; Heryani, Heni (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2025)
Introduction: Pregnancy causes physical and psychological changes. Psychological changes, such as emotional changes, anxiety, and anxiety disorders, also make it difficult for mothers to sleep. The prevalence of insomnia as one of the sleep disorders in pregnant women worldwide reaches 41.8%, with a total of around 58.52 million people. In Indonesia, according to the National Sleep Foundation survey, there are 5,354,594 pregnant women, and in West Java there are 138.53 thousand. In Ciamis Regency, the Health Office in 2024 recorded a total of 20,851 pregnant women. Objective: This study aims to determine the effect of pregnancy exercises on the quality of sleep of third trimester pregnant women in Sindangrasa Village, Ciamis Regency.  Method: This study used a quantitative method with a quasi-experiment design. Treatment in the form of pregnant gymnastics was given, then a post-test was conducted to measure the respondents' sleep quality after treatment. The research was conducted on December 1-21, 2024 with 10 respondents in Sindangrasa Village, Ciamis Regency. Result: The results showed that before the pregnancy exercise, most pregnant women had poor sleep quality as many as 8 people (80%). After doing pregnancy exercises, most pregnant women experienced an increase in good sleep quality as many as 9 people (90%). The results of the Wilcoxon Test resulted in a p value = 0.007 which indicates the effect of pregnant gymnastics on the quality of sleep of third trimester pregnant women. Conclusion: Based on the results of the study, it was concluded that pregnancy exercises have a positive effect on the quality of sleep of third trimester pregnant women in Sindangrasa Village, Ciamis Regency.